Analysis of the Water Availability to Irrigation Needs in Irrigation Areas Jambo Aye - ., Wesli; Jalalul Akbar, Said (International Journal of Engineering and Technology, 2018)
Jambo Aye Irrigation Area serves cross-district irrigation water needs, namely North Aceh district and East Aceh district with a service area of 19,360 Ha and in accordance with the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14/PRT/M/2015, criteria and determination of the status of irrigation areas is the authority of the Central Government. Complaints of farmers' communities, especially in North Aceh, there is always a shortage of water for the needs of rice fields, this can be caused by a lack of water supply or it could be caused by damage to irrigation infrastructure. In this study, the availability of water was analyzed from sources for irrigation needs by looking at the water balance. The research method uses the Mock method because there is no discharge measurement data in the study area. The results of the study illustrate that monthly water demand is smaller than the available water called monthly reliable discharge. Water shortages experienced by farmers are not due to supply shortages that are considered possible due to damage to irrigation infrastructureÂ